PHYSICAL ACTIVITY PROMOTION PROGRAM DURING COVID - 19 PANDEMIC USING ECOLOGICAL FOR UNDERGRADUATE STUDENTS - Phuttarakkit, Phonphol; Sarayutthpitak, Jintana; Rodpipat, Sarinya; Phroedphring, Chatchana (Academic Journal of Thailand National Sports University, 2023)
Purposes: 1) To compare the mean scores of physical activity knowledge and physical activity behavior before and after the experiment of the students in the experimental group who received the physical activity promotion program by using the ecological model. and the students in the control group who did not receive physical activity promotion program by using the ecological model, 2) To compare the mean scores of physical activity knowledge and physical activity behavioral after the experiment between the experimental group and the control group. Method: The subjects consisted of 50 undergraduate students, divided into 2 groups with a matching method, 25 students in the experimental group and 25 students in the control group. The research instrument was the program to promote physical activity in the situation of the COVID - 19 epidemic using an ecological model consisting of 8 activities: 1) YOU KNOW 2) YOU CAN 3) Fit at Home: Body weight 4) Fit at Home: Yoga 5) Fit at Home: Games 6) Fit at Home: Dance 7) Fit at Home: Walk and Run 8) Fit at Home: With IOC of an 0.95, and the data collection instruments included a physical activity knowledge measurement form and physical activity behavior assessment form with IOC of 0.8 and 1, reliability of 0.81 and 0.81, respectively. The duration of the experiment was 8 weeks. 3 days a week, 40 minutes a day, The data were analyzed by mean, standard deviation and t - test. Results: The research findings were as follows: 1) The mean scores of physical activity knowledge and physical activity behavior scores of the experimental group were significantly higher than that before the experiment. 2) The mean scores of physical activity knowledge and physical activity behavior of the experiment group after the experiment were significantly higher than that in the control group at the .05 level. Conclusion: Physical activity promotion program in the situation of COVID – 19 epidemic by using ecological model affected knowledge of the physical activity and physical activity behavior score of graduate students.